Experimental quantification of site-specific efficiency of Interatomic Coulombic Decay after inner shell ionization - Küstner-Wetekam, Catmarna; Marder, Lutz; Bloß, Dana; Honisch, Carolin; Kiefer, Nils; Richter, Clemens; Rubik, Simon; Schaf, Rebecca; Zindel, Christina; Förstel, Marko; Gokhberg, Kirill; Knie, André; et al. (Communications Physics, 2023)
Interatomic Coulombic Decay (ICD) and related interatomic and intermolecular autoionization mechanisms are ubiquitous decay processes of excited atoms and molecules in an environment. It is commonly accepted that the efficiency of ICD of an ionized atom in a cluster increases with an increasing number of nearest neighbors. Here, we present a method for experimental validation of this assumption by a site-specific and quantitative comparison of ICD and its main competitor, Auger decay, in core-level ionized Kr clusters. Our results are in quantitative agreement with scaled theoretical calculations on Kr2.